Pengaruh Fasilitas Terhadap Kepuasan Pasien Di Klinik Marhamah - Ramdhani, Bilal Mahardhika; Fadili, Dadan Ahmad (Jurnal Ilmiah Wahana Pendidikan, 2024)
In : This study uses a quantitative method that is descriptive and causal. The population in this study were patients who had been treated at the Marhamah Clinic for the 2021-2022 period. The sampling technique in this study is probability sampling with simple random sampling method. The sample in this study used the Slovin calculation method of 5% so that a sample of 394 patients was obtained in this study. Based on the results of the study, the coefficient of determination showed that the effect of facilities on Marhamah Clinic patient satisfaction was 29%, while the remaining 71% was influenced by other factors not examined in this study. This study concludes that facilities have a significant effect on patient satisfaction at Marhamah Clinic.